2007
DOI: 10.3317/jraas.2007.004
|View full text |Cite
|
Sign up to set email alerts
|

Review: Lisinopril in paediatric medicine: a retrospective chart review of long-term treatment in children

Abstract: Objective. To investigate the antihypertensive efficacy, dosing, tolerability and effects on growth of lisinopril (off label-use) in paediatric patients during long-term treatment. Design. We conducted a retrospective analysis of data from 123 patients treated with lisinopril in a paediatric nephrology clinic over a 9.3-year period. Patients were categorised by age group and predominant clinical diagnosis: hypertension (n=59), renal parenchymal disease (n=27), diabetes mellitus (n=33) and miscellaneous (n=4).R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Two of the studies defined hypertension as a DBP of ≥95th percentile for age, gender and height on repeated measurements, according to the ‘Fourth Report’ 1 15 17. In contrast, an SBP of ≥95th percentile was used in two studies, and an SBP or a DBP of ≥95th percentile was used in three studies 14 16 18–20. Soergel et al ,21 Seeman et al 25 and Wühl et al 22,24 defined hypertension as 24-hour mean systolic or diastolic arterial pressure ≥95th percentile for age, gender and height.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the studies defined hypertension as a DBP of ≥95th percentile for age, gender and height on repeated measurements, according to the ‘Fourth Report’ 1 15 17. In contrast, an SBP of ≥95th percentile was used in two studies, and an SBP or a DBP of ≥95th percentile was used in three studies 14 16 18–20. Soergel et al ,21 Seeman et al 25 and Wühl et al 22,24 defined hypertension as 24-hour mean systolic or diastolic arterial pressure ≥95th percentile for age, gender and height.…”
Section: Resultsmentioning
confidence: 99%
“…Lisinopril administration in hypertensive children has also been evaluated in a retrospective study and was found to result in a decrease in both SBP and DBP 16. The efficacy of lisinopril has also been evaluated in children with a renal transplant in a 30-day pharmacokinetic study and was also found to decrease both SBP and DBP with ≥6 mm Hg in 85% and 77%, respectively 23…”
Section: Resultsmentioning
confidence: 99%
“…Enalapril and lisinopril both produce a dose-dependent reduction in blood pressure. Minimum effective dosages range from 0.08 mg/kg/day to 0.6 mg/kg/day and were well tolerated 12,27,28. However, fosinopril did not produce the same dose response reduction in blood pressure as that seen in the enalapril and lisinopril studies, but did demonstrate a significant reduction in SBP and DBP.…”
Section: Clinical Studies Safety and Efficacymentioning
confidence: 89%
“…One study found that children between 2–16 years of age receiving enalapril or captopril developed neutrophilic hypersegmentation 30. One retrospective study of lisinopril found no effect on age-specific growth patterns despite the varying medical conditions of the participants 28. A meta-analysis of studies evaluating ethnic differences in children treated with ACEI suggested a difference between black and white children to the antihypertensive effects of ACEI.…”
Section: Clinical Studies Safety and Efficacymentioning
confidence: 99%
“…Lisinopril (LIS), (S)‐1‐[N 2 ‐(1‐carboxy‐3‐phenylpropyl)– l ‐lysyl]– l ‐proline, (Fig. S1, Supporting Information) is a long‐acting angiotensin‐converting enzyme (ACE) inhibitor, widely used in therapy for the treatment of many disorders including hypertension, heart failure, acute myocardial infarction, and diabetic nephropathy …”
Section: Introductionmentioning
confidence: 99%